Comparative Study of Equations of State (University of Khartoum Engineering Journal, 2022)
The objective of this work is to predict thermodynamic properties of pure component using equation ofstate (EOS). Six EOSs used in this study, namely Soave-Redlich-Kwong (SRK), Peng-Robinson (PR), Schmidt-Wenzel (SW), Patel-Teja (PT), Lawal-Lake-Silberberg (LLS), and Adachi-Lu-Sugie (ALS). The pure componentused include eleven hydrocarbon compounds from methane to normal decane and four non-hydrocarboncompounds namely water, hydrogen sulphide, nitrogen, and carbon dioxide. The predicted properties includevapor pressure, saturated vapor and liquid volumes, in temperature range from triple to critical point. A computercode using Matalab software is written to facilitate the calculation. The predicted resulted is compared withexperimental data. The results reveled with exception SW EOSs all EOSs are inconsistent in the prediction ofthermodynamics properties of the fluids under consideration. SW predicted all properties with absolute averagepercent deviation (AAPD) of less that 3